Albert speer : architecture 1932-1942 - Krier, Leon.; Stern, Robert A. M. ([S.l.] : The Monacelli Press, 2013)
Architect Léon Krier asks, Can a war criminal be a great artist? Speer, Adolf Hitler's architect of choice, happens to be responsible for one of the boldest architectural and urban oeuvres of modern times. First published in 1985 to an acute and critical reception, Albert Speer: Architecture 1932-1942 is a lucid, wide-ranging study of an important neoclassical architect. Yet is is simultaneously much more: a philosophical rumination on art and politics, good and evil. With aid from a new introduction by influential American architect Robert A. M. Stern, Krier candidly confronts the great difficulty of disentangling the architecture and urbanism of Albert Speer from its political intentions. Krier bases his study on interviews with Speer just before his death. The projects presented center on his plan for Berlin, an unprecedented modernization of the city intended to be the capital of Europe.
Keywords: Architecture; Germany--Berlin; National socialism and architecture; Speer, Albert, 1905-1981; Themes, motives